ATTENTION TO WOMEN AND GIRLS IN THE NEW UZBEKISTAN (International journal of artificial intelligence, 2025)
A woman is the main pillar of society and a sacred being who shapes the future of humanity. Her qualities like motherhood, compassion, selflessness, patience and social responsibility define her sanctity. The role of women in society is increasing not only in the family, but also in science, culture, politics and economy. Ensuring women's rights, equality and freedom, increasing her spiritual maturity and contributing to the development of society is very important. This article talks about the sanctity of women and their place in society, as well as the need to respect and pay attention to her values.